Why Do Temporary Help Firms Provide Free General Skills Training? - Autor, D. H. (Quarterly Journal of Economics, 2001)
The majority of U. S. temporary help supply (THS) firms offer nominally free, unrestricted computer skills training, a practice inconsistent with the competitive model of training. I propose and test a model in which firms offer general training to induce self-selection and perform screening of worker ability. The model implies, and the data confirm, that firms providing training attract higher ability workers yet pay them lower wages after training. Thus, beyond providing spot market labor, THS firms sell information about worker quality to their clients. The rapid growth of THS employment suggests that demand for worker screening is rising.